Funding Growth in Bank-Based and Market-Based Financial Systems : Evidence from Firm-Level Data - Demirguc-Kunt, Asli; Maksimovic, Vojislav (World Bank, Washington, DC, 2014)
The authors investigate whether firms' access to external financing, to fund growth differs between market-based, and bank-based financial systems. Using firm-level data for forty countries, they compute the proportion of firms in each country that relies on external finance, and examine how that proportion differs across financial systems. They find that the development of a country's legal system predicts access to external finance, and that stock markets, and the banking system have different effects on access to external markets. The development of securities markets is related more to the availability of long-term financing, whereas the development of the banking sector is related more to the availability of short-term financing. They find no evidence, however, that firms' access to external financing is predicted by an index of the development of stock markets, relative to the development of the banking system.